Electrochemical capacitance of intermetallic vanadium carbide. (December 2020) - Zhang, Lun; Zhang, Wei-Bin; Zhang, Qiang; Bao, Xu; Ma, Xue-Jing
Abstract: The polycrystalline intermetallic vanadium carbide (V8 C7 ) is successfully synthesized and investigated as an electrode material for electrochemical capacitors. The V8 C7 electrode has a large specific capacitance of 161.7 F g −1 in 1.0 mol L −1 Na2 SO4 at a specific current density of 1 A g −1 and remains 92.8% of this value after 10, 000 cycles. 83.3% of the initial value can maintain even at a high current density of 10 A g −1 . The outstanding electrochemical performance is attribute to the high electrical conductivity of V8 C7 which can ensure fastly charge transfer. Combined with the analysis of specific capacitances and specific surface areas, the charge storage mechanism belongs to the sub-surface space pseudocapacitive mechanism. Moreover, the V8 C7 //activated carbon asymmetrical electrochemical capacitor owns a high energy density of 16.9 W h kg −1 at a power density of 8.7 kW kg −1 . Highlights: An intermetallic of vanadium carbide is synthesized by nanoscaled solidoid. Specific surface areas are ruled using heating rates of pyrolysis of precursor. The vanadium carbide is used for capacitive electrode material successfully. Pseudo-capacitive property is investigated by surface area and capacitance.